Evaluation of English Teaching Material for Senior High School - Astrini, Atik; Yeny Prastiwi; Muamaroh (Journal of International Multidisciplinary Research, 2023)
In Surakarta, English teachers use manuals to guide scholars and collaborate in the literacy process, and use it as a tonal resource to gain rich input into literacy. In order to improve the quality of English teaching in Indonesia, this study was conducted to measure whether  two books used in high school, "English for Critical Thinking" and "Bahasa Inggris Tingkat Lanjut" are correct or not. This research used Alan Cunningsworth's suggestion of an excellent text and tried to find the strengths and weaknesses of the two books based on the given styles. The study was conducted using an evaluation survey to evaluate two manuals in English  used by some seminaries in Surakarta. The evaluation method involved sampling books to see if they met criteria for good textbooks developed by the experimenter based on Cunningsworth's framework. The study found that Bahasa Inggris Tingkat Lanjut fulfills the five objectives and approaches of standard, design and association, content, teacher's book and policy perspective. English For Critical Thinking Allowing completes four excellent texts on Cunningsworth's goals and approaches, design and association, a teacher's book, and political attention. Bahasa Inggris Tingkat Lanjut meets five principles of Cunningsworth's excellent example and styles, design and association, pieces, content and teacher's book. The experimenter also noticed that the strengths and weaknesses of "English For Critical Thinking" and "Bahasa Inggris Tingkat Lanjut". Based on the results, the experimenter recommends that the teacher use two manuals in the teaching-literacy process because two books meet the criteria of a good book.